Portable Art-Based Museum Workshops - Loukia Chaidemenaki; Despoina Vaxevanidi; Erifyli Papakonstantinou; Spiridoula Fideropoulou (The International Journal of the Inclusive Museum, 2026)
Engagement with arts and cultural activities is increasingly recognized as beneficial for mental health; however, in Greece, there remains limited evidence regarding outreach museum programs for clinical populations. This study evaluates the Portable Art Therapy Museum Workshop, an initiative designed to examine the impact of a museum-based outreach program on the well-being of young people with severe mental health challenges, following a psychosocial approach. An art-based mixed-methods design was employed. Nineteen participants (aged 17–30 years, M = 22) from mental health community services engaged in a five-session portable workshop (museum visits and art as therapy workshops). Well-being was measured pre- and post-program using the University College London (UCL) Museum Wellbeing Wheel and analyzed with the Wilcoxon signed-rank test. Art-based qualitative observation and analysis identified three themes: Museum as Meeting Point, Self Objects, and My Personal Museum. UCL Wellbeing Wheel results showed a statistically significant improvement in psychological well-being (p < .001) before and after participation. Qualitative observations suggest that art objects can have multiple subjective and cultural meanings and therapeutic effects through memory and identity; that this approach helps to reduce practical, psychological, and symbolic barriers to social and cultural participation; and that it can enhance psychological well-being for young adults with severe mental health challenges.